Enzyme‐Embedded Metal–Organic Framework Colloidosomes via an Emulsion‐Based Approach. Issue 19 (27th August 2018) - Zhu, Guixian; Zhang, Mizhen; Bu, Yang; Lu, Lidan; Lou, Xiaoping; Zhu, Lianqing
Abstract: Improving the activity and stability of enzymes is significant in enzyme immobilization. Here a facile approach to prepare ring‐like ZIF‐8 colloidosomes and spherical catalase‐embedded ZIF‐8 colloidosomes is developed via one‐step emulsion‐based technique at the water/butanol interface. The influence of the concentrations of ZIF‐8 nanocrystals and Pluronic F127 as well as the oil‐water ratio was investigated. Compared with in situ biomineralization, the colloidosomes prepared via the pickering emulsion method show successful encapsulation of positively charged enzymes. By using catalase as an immobilized model, the immobilized catalase exhibits high biocatalytic activity, stability and recyclability compared with free catalase. Abstract : Emulsion‐based approach : A facile method to prepare ring‐like ZIF‐8 colloidosomes and spherical catalase‐embedded ZIF‐8 colloidosomes is developed at water/butanol interface via one‐step emulsion‐based technique. Compared with free catalase, the immobilized catalase exhibits great biocatalytic activity, stability and recyclability.